2021
DOI: 10.1186/s13223-020-00503-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Polyvalent Mechanical Bacterial Lysate on lymphocyte number and activity in asthmatic children: a randomized controlled trial

Abstract: Background Polyvalent Mechanical Bacterial Lysate (PMBL®) contains antigens of bacteria responsible for respiratory infections. PMBL® has been proven to reduce the number of respiratory infections, and in its use, immunological benefits have been seen in allergic patients. PMBL® activates both innate and specific immune responses. The lysate induces dendritic cells, T and B lymphocytes and IgA secretion, as well as the production of antibodies directed against administered bacterial antigens. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
13
0
1
Order By: Relevance
“…IL-12 and IL-18 promoted by BLs stimulate NK1 polarization, which results in enhanced IFN-g secretion and IgE production suppression (88). The study by Bartkowiak-Emeryk et al showed an increase of NK cells in asthmatic children sublingually treated with PMBL (57). Moreover, DCs exposed to PCBL released increased levels of CCL2 and CCL3, chemokines important for chemoattraction of monocytes and NK cells (31).…”
Section: Macrophages and Nk Cells Activationmentioning
confidence: 99%
See 3 more Smart Citations
“…IL-12 and IL-18 promoted by BLs stimulate NK1 polarization, which results in enhanced IFN-g secretion and IgE production suppression (88). The study by Bartkowiak-Emeryk et al showed an increase of NK cells in asthmatic children sublingually treated with PMBL (57). Moreover, DCs exposed to PCBL released increased levels of CCL2 and CCL3, chemokines important for chemoattraction of monocytes and NK cells (31).…”
Section: Macrophages and Nk Cells Activationmentioning
confidence: 99%
“…However, as the data suggest, it can be assumed that the period in which the therapy is started is essential in the case of seasonal allergic diseases. For instance, the treatment plan in seasonal AR (SAR) usually consists of prescribing one PMBL tablet sublingually per day for 10 days with 20 days of a break for three consecutive months, and the treatment should preferably be started a few days before the beginning of the pollen season ( 57 ). In a perennial AR (PAR), the dosing regimen is the same as described above; however, it is assumed that in this group of patients, repeating this regimen twice per year may provide additional benefits ( 58 ).…”
Section: Bacterial Lysatesmentioning
confidence: 99%
See 2 more Smart Citations
“…The absolute number of NK cells significantly increased by 56% in 28 COPD patients treated with PMBL [ 10 ]. A randomized controlled trial has shown an increase in NK cell count in 21 asthmatic children compared to the control group after PMBL treatment [ 27 ]. Our study showed a significant increase in IFN-γ levels in 301 patients treated with PMBL.…”
Section: Discussionmentioning
confidence: 99%